Zdravila za zdravljenje pljučne arterijske hipertenzije - Petrovič, Maja (Farmacevtski vestnik, 2015)
Pulmonary arterial hypertension (PAH) is a rare, chronic and progressive disease of various aetiologies, and affects pulmonary vessels. Irrespective of the cause, pathological changes to pulmonary vasculature lead to right ventricular dysfunction and premature death. The development of new drugs in the treatment of PAH has been accelerated over the last two decades, also on the initiative of the European Commission. In the last three years two new drugs for the treatment of PAH were approved, while the approval for the third drug is anticipated. Specific drug therapy used in the treatment of PAH is presented in the article, namely prostacyclin analogues, selective prostacyclin agonists, endothelin receptor antagonists, phosphodiesterase 5 inhibitors, and soluble guanylate cyclase stimulators.
Keywords: pljučna arterijska hipertenzija; specifična zdravila; prostaciklin; uporaba zdravil; antagonisti endotelinskih receptorjev; primerno zdravljenje